Quantification of iodiconazole by LC–MS/MS, a new topical transdermal cream, in dermatophytosis patients' plasma. (April 2015) - Zhao, Hui; She, Xiao Dong; Yu, Xia Xia; Fu, Jin Feng; Chen, Yun; Tian, Yuan; Zhang, Zun Jian
Background: A rapid and sensitive LC–MS/MS method was established to measure iodiconazole (ADKZ) in dermatophytosis patients treated topically with 2% ADKZ cream.Methodology: ADKZ was extracted by liquid-liquid extraction (LLE) and separated by an Agilent Zorbax SB-C18 column (2.1 × 150 mm, 3.5 μm) using methanol – 0.01% formic acid (70:30, v/v) as the mobile phase. All the validation assays met the acceptable criteria and the linearity ranged from 10 to 1000 pg/ml.Conclusion: The method has been validated to be simple, sensitive and successfully applied to the study. The average amount of ADKZ absorbed into blood was approximately 0.51 μg daily, and ADKZ blood concentrations were consistent during the four-week treatment course. The cumulation of ADKZ in vivo was almost negligible.